V-Y Rotation Advancement Flap for Sacral Sore: Experiences at Rajshahi - Nazneen, Afroza; Adnan, Md Nafis Alam (TAJ: Journal of Teachers Association, 2022)
Grade III and Grade IV sacral pressure sores are required surgical closure. The gluteal fascio-cutaneous rotation advancement flap with V-Y closure was performed in our hospital on 50 cases of sacral sore from 2017 to 2019. The largest defects closed with a unilateral flap were up to 14 cm, and a bilateral flap needed to close 15-22 cm in diameter. In 1.5 to 24 months of follow-up time, none of the patients developed wound dehiscence or flap necrosis requiring repeated surgery. The V-Y rotation advancement flap technique is simple, can be performed quickly, has minimal associated morbidity, and has a good outcome. Furthermore, we can use the same flap design in recurrent cases. TAJ 2022; 35: No-1: 33-38